Effect of Temperature, Time, and Material Thickness on the Dehydration Process of Tomato - A. F. K. Correia; A. C. Loro; S. Zanatta; M. H. F. Spoto; T. M. F. S. Vieira (International Journal of Food Science)
This study aimed to evaluate the effects of temperature, time, and thickness of tomatoes fruits during adiabatic drying process. Dehydration, a simple and inexpensive process compared to other conservation methods, is widely used in the food industry in order to ensure a long shelf life for the product due to the low water activity. This study aimed to obtain the best processing conditions to avoid losses and keep product quality. Factorial design and surface response methodology were applied to fit predictive mathematical models. In the dehydration of tomatoes through the adiabatic process, temperature, time, and sample thickness, which greatly contribute to the physicochemical and sensory characteristics of the final product, were evaluated. The optimum drying conditions were 60°C with the lowest thickness level and shorter time.